2023
DOI: 10.1002/eap.2811
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated alien plants with high invasion potential are more likely to be traded online in China

Abstract: Biological invasions have become a worldwide problem, and measures to efficiently prevent and control invasions are still in development. Like many other parts of the world, China is undergoing a dramatic increase in plant invasions. Most of the currently 933 established (i.e., naturalized) plant species, of which 214 are categorized as invasive, have been introduced into China for cultivation. It is likely that many of those species are still being traded, particularly online, by plant nurseries. However, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Global plant trade networks emerged in the 18th and 19th centuries when alien plants began to appear frequently in non–native wild areas, particularly in the 19th century [ 48 ]. Increased trade in species, the complexity of trade networks, improved long–distance connectivity, and new trade patterns contributed to S. viarum invasion [ 49 ]. As a major source of pharmaceutical compounds (especially solasodine), S. viarum established colonies along trade routes and rapidly expanded during this phase.…”
Section: Discussionmentioning
confidence: 99%
“…Global plant trade networks emerged in the 18th and 19th centuries when alien plants began to appear frequently in non–native wild areas, particularly in the 19th century [ 48 ]. Increased trade in species, the complexity of trade networks, improved long–distance connectivity, and new trade patterns contributed to S. viarum invasion [ 49 ]. As a major source of pharmaceutical compounds (especially solasodine), S. viarum established colonies along trade routes and rapidly expanded during this phase.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the latter, we found that, at least for long‐lived herbaceous and woody species, online‐nursery availability was positively related to economic use. Previous studies have pointed out the importance of the offline plant‐nursery‐supply chain as the driver of plant naturalization and invasiveness (Beaury et al., 2021; Hulme et al., 2018; Pemberton & Liu, 2009), but the role of online plant nurseries has been rarely considered (Dong et al., 2023; Humair et al., 2015). Because the online trade in plants started only a few decades ago, it cannot be a cause of plant invasions that happened half a century ago.…”
Section: Discussionmentioning
confidence: 99%
“…These species, frequently traded online, continue to increase invasion risks. Through a synthesis evaluation, Dong et al (2023) found that naturalized noninvasive and invasive plant taxa were more likely to be available for purchase. The implementation of stringent plant trading regulations and monitoring of online horticulture supply chains is urgently needed to mitigate the further spread of these invasive species.…”
Section: Risk Analysismentioning
confidence: 99%